Muscle pain as a regulator of cycling intensity: effect of caffeine ingestion - Gonglach, A. R.; Ade, C. J.; Bemben, M. G.; Larson, R. D.; Black, C. D. (Medicine & Science in Sports & Exercise, 2016)
Caffeine ingestion improves endurance time trial performance. However, the ergogenic mechanism of action remains unresolved. One potential explanation for caffeine`s performance-enhancing effect is an improvement in work for a given amount of muscle pain.